Universal miniplate holder - A novel invention in the field of maxillofacial trauma - B. Nithin Joseph Jude, MDS; Suresh kumar Ganesan, MDS; Nathiya Balasubramaniyan, MDS; K. Raghu, MDS; P. Mohammed Rafeeq, MDS (Elsevier, 2022)
The present invention discloses an Universal Miniplate holder to hold and stabilize miniplate.